2004
DOI: 10.1042/bj20030969
|View full text |Cite
|
Sign up to set email alerts
|

Detergents profoundly affect inhibitor potencies against both cyclo-oxygenase isoforms

Abstract: The sensitivity of Coxs (cyclo-oxygenases) to inhibition is known to be highly dependent on assay conditions. In the present study, the inhibitor sensitivities of purified Cox-1 and -2 were determined in a colorimetric assay using the reducing agent N, N, N ', N '-tetramethyl- p -phenylenediamine. With the detergent genapol X-100 (2 mM) present, the potencies of nimesulide, ibuprofen, flufenamic acid, niflumic acid and naproxen were increased over 100-fold against Cox-2 and titration curve shapes changed, so t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 48 publications
(69 reference statements)
2
16
0
Order By: Relevance
“…The effects of the detergents on the inhibitors' potency were complex and were not interpreted in terms of a unified mechanism. The PC was reported to increase the inhibitory potency of ibuprofen and flufenamic acid, fitting the pattern observed with several nonionic detergents (7). The present results with structurally defined DOPC liposomes and a simple, reversible competitive inhibitor (ibuprofen) showed roughly 5-fold increases in the inhibitor's potency against both COX-1 and -2 (Fig.…”
Section: Phospholipids and Cox Inhibitor Actionssupporting
confidence: 66%
See 3 more Smart Citations
“…The effects of the detergents on the inhibitors' potency were complex and were not interpreted in terms of a unified mechanism. The PC was reported to increase the inhibitory potency of ibuprofen and flufenamic acid, fitting the pattern observed with several nonionic detergents (7). The present results with structurally defined DOPC liposomes and a simple, reversible competitive inhibitor (ibuprofen) showed roughly 5-fold increases in the inhibitor's potency against both COX-1 and -2 (Fig.…”
Section: Phospholipids and Cox Inhibitor Actionssupporting
confidence: 66%
“…This interpretation envisages that, unlike the case of ibuprofen, some inhibitors may actually partition into phospholipid bilayers more effectively than arachidonate and thus have their potency decreased. This provides a potential explanation for the otherwise puzzling observation that detergent micelles decreased the potency of some COX inhibitors (7). There are also kinetic considerations.…”
Section: Mechanism Of Action Of Phospholipid On Cox Inhibitor Potencymentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, LOR inhibited ovine COX-1 activity at 10 -8 mol/l but had little inhibitory effect on COX-1 at high concentrations. Although the effects of the reference compound DuP-679 were not investigated on ovine COX-1 in this study, it has previously been shown to inhibit COX-1 at high doses [19] . Following the studies on ovine COX-1 and COX-2 enzymes with FEX, isolated human COX-2 became available for testing.…”
Section: Discussionmentioning
confidence: 99%